Nostalgia Marketing: Pendekatan Komunikasi Strategis Untuk Menarik Minat Wisatawan Pasar Kangen Yogyakarta - Sheila Lestari Giza Pudrianisa; Muhammad Thoyib Amali (Jurnal Riset Komunikasi (JURKOM), 2025)
Yogyakarta is a city famous for its cultural, traditional and tourism elements. However, data from 2022-2023 shows that the number of tourist visits did not increase even though the pandemic was over. Therefore, the local government paid special attention and tried to realize creative products based on traditional and popular culture in the form of an event called Pasar Kangen. This event is quite unique and different because it carries the concept of presenting the nuances of the past in each element. From this problem, the researcher analyzed how the strategic communication approach used in the Nostalgia marketing element is effective in attracting tourists to the Pasar Kangen Yogyakarta. The theory used is nostalgia marketing with a descriptive qualitative method. The results of the study are through 4 approaches, the first is personal nostalgia in the form of the presence of typical food/snacks from various regions which are served traditionally. Interpersonal nostalgia through the presence of antique goods/toys that remind us of the atmosphere of the past. Cultural nostalgia through arts such as dance/nyanyain which are presented as an entertainment stage and virtual nostalgia, namely consumers can feel the atmosphere of Pasar Kangen through social media. Pasar Kangen has succeeded in presenting and reviving past memories for consumers so that it can be used as an effective strategy to increase tourist visits.